HUBUNGAN ANTARA IKLIM ORGANISASI DAN PENGETAHUAN KOMUNIKASI DENGAN KINERJA GURU SMP NEGERI SE-KECAMATAN KETAHUN - Warsito Warsito Warsito (Manajer Pendididikan, 2016)
The objective of this research is to analize the correlation of organizational climate with the performance of teachers, the relationship of knowladge communications with the performanceof teachers, and the relationship of organizational climate and knowledge of communication together with the performance of teachers. Samples of this research were junior high schoolteachers throughout the District Ketahun. Correlation descriptive research method applied in this study. The results showed that: there is a positive correlation between organizational climate with the performance of teachers, there is a positive correlation between knowledge of communication and teacher performance, and there is a positive correlation between organizational climate and knowledge of communication together with the performance of teachers.Keywords: organizational climate, communication science, teacher performance